Soil Respiration and Carbon Balance Under Cover Crop in a no-Till Tropical Fruit Orchard - Freidenreich, Ariel; Dattamudi, Sanku; Li, Yuncong C.; Jayachandran, Krishnaswamy (Frontiers in Environmental Science, 2021)
Agricultural practices, specifically crop and land management schemes, greatly influence the ability of soil to produce CO2 under varying conditions. A two-year research study was planned to quantify carbon-dioxide (CO2) emission fluxes and total C (TC) contribution in a no-till tropical soil under carambola with sunn hemp-velvet bean cover cropping (CC) systems. Composted poultry manure (PM) was applied as an additional N source. The treatments were fallow control (F), fallow with PM (FM), sunn hemp (SH), SH with PM (SHM), velvet bean (VB), and VB with PM (VBM). Average daily CO2 emission from VB was 23 and 15% higher than control and SH plots, respectively, during CC growing season. Similarly, CO2 emission after CC termination was highest from VB plots. About 17% higher CO2-C emission was observed from manure applied plots which indicates that additional food sources stimulated microbial activity in the soils and subsequently produced more CO2. However, total C contribution in SH plots were significantly higher than in VB plots, and was more apparent when manure was not applied. Soil and air temperature played key roles in CO2 emission, specifically during the CC growing season. Considering both input and output parameters of C in the soil, our results suggest that SH has the better potential in reducing CO2 emission and accumulating more C in the soil than VB in tropical fruit orchard.